Preparation method of antibacterial tent fabric

By using a combination coating of silicone modified water-based polyurethane and antibacterial materials on the tent fabric, the problem of poor antibacterial performance of tent fabrics is solved, and long-term antibacterial effect and water resistance are achieved, ensuring that the tent maintains antibacterial function during long-term use. .

CN119308146APending Publication Date: 2025-01-14NANTONG ABLE OUTDOOR PROD COMPANY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411536830.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The antibacterial performance of existing tent fabrics is not ideal, and the antibacterial coating has a short service life, which can easily lead to the tent losing its antibacterial function.

Method used

Silicone modified water-based polyurethane is used as the main constituent material of antibacterial coating, and the antibacterial coating is coated on the surface of the base cloth, including antibacterial materials such as graphene, nanotitanium dioxide and nanosilver, fillers such as bentonite and concave and concave rod soil, through plasma Pretreatment improves the coating bonding effect and forms a long-acting antibacterial tent fabric.

Benefits of technology

It improves the water resistance and water washing resistance of the antibacterial coating, extends the antibacterial properties of the tent, ensures the integrity and antibacterial effect of the coating in long-term use, and enhances the hydrophobicity and density of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005111758620000081
    Figure BDA0005111758620000081
  • Figure BDA0005111758620000091
    Figure BDA0005111758620000091
  • Figure BDA0005111758620000101
    Figure BDA0005111758620000101
Patent Text Reader

Abstract

The invention relates to the technical field of tent fabrics, and particularly discloses a preparation method of an antibacterial tent fabric. According to the preparation method of the antibacterial tent fabric, the antibacterial tent fabric comprises base cloth and an antibacterial coating coated on the surface of the base cloth, and the antibacterial coating comprises the following raw materials in parts by weight: 40-45 parts of waterborne polyurethane; 5-15 parts of an antibacterial material; 10 to 20 parts of filler; 5 to 10 parts of polyacrylic acid dispersion; 1-2 parts of a defoaming agent; 1-3 parts of a lubricant; 1-3 parts of an isocyanate curing agent; the waterborne polyurethane is organic silicon modified waterborne polyurethane; the preparation method comprises the following steps: S1, preparing the antibacterial coating; s2, base cloth pretreatment; and S3, preparing the tarpaulin. The tent fabric can be used in outdoor tents, and has the advantages of high water resistance, lasting antibacterial property and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of tent fabrics, and more specifically, to a method for preparing antibacterial tent fabrics. Background Art

[0002] In recent years, outdoor camping, outdoor sports and other activities have become the mainstream outdoor activities, and the demand for tents has also increased. Tents are composed of tent fabrics and other accessories. The tent fabrics are made of relatively strong fabrics such as polyester, nylon, and Oxford cloth. The outdoor environment is complex and there are many bacteria and microorganisms, which can easily cause harm to the human body. Therefore, the antibacterial function of tents becomes particularly important, and the development of antibacterial tent fabrics also becomes particularly important.

[0003] At present, in order to make tent fabrics have antibacterial effects, antibacterial coatings are mostly applied on the surface of tent fabrics to achieve the antibacterial effect. However, the antibacterial performance of most treated tent fabrics is not ideal, and the service life of the antibacterial coating is short. If it is used too many times, it is easy to cause the tent to no longer have antibacterial properties. Therefore, it is urgent to further improve the antibacterial effect of tent fabrics. Summary of the invention

[0004] In order to improve the antibacterial effect of tent fabrics, the present application provides a method for preparing antibacterial tent fabrics, which adopts the following technical solutions:

[0005] The present application provides a method for preparing an antibacterial tent fabric, comprising a base fabric and an antibacterial coating coated on the surface of the base fabric, wherein the antibacterial coating comprises the following raw materials in parts by weight:

[0006] 40-45 parts of waterborne polyurethane;

[0007] 5-15 parts of antibacterial materials;

[0008] 10-20 parts of filler;

[0009] 5-10 parts of polyacrylic acid dispersion;

[0010] 1-2 parts of defoaming agent;

[0011] 1-3 parts of lubricant;

[0012] 1-3 parts of isocyanate curing agent;

[0013] The waterborne polyurethane is silicone-modified waterborne polyurethane;

[0014] The preparation of the antibacterial tent fabric comprises the following steps:

[0015] S1. Preparation of antibacterial coating: taking waterborne polyurethane, antibacterial material, filler, polyacrylic acid dispersion, defoamer, lubricant and isocyanate curing agent respectively by weight, stirring and mixing to obtain antibacterial coating;

[0016] S2, base fabric pretreatment: performing plasma treatment on the base fabric to obtain a pretreated base fabric;

[0017] S3. Tarpaulin preparation: coating the surface of the pretreated base fabric with an antibacterial coating, and drying the pretreated base fabric to prepare an antibacterial tent fabric.

[0018] By adopting the above technical scheme, silicone-modified water-based polyurethane is used as the main component material of the antibacterial coating. The introduction of silicone chain segments can make the water-based polyurethane obtain better water resistance, and then the antibacterial coating obtains excellent water resistance and water washing resistance, so that the tent can maintain the integrity of the coating during long-term use, and the coating is not easy to be washed and peeled off, that is, the antibacterial coating has a long-lasting antibacterial effect.

[0019] The base fabric is preferably pretreated. The surface of the base fabric pretreated with plasma obtains more active groups, which effectively improves the bonding effect between the base fabric and the antibacterial coating, further reduces the possibility of the antibacterial coating falling off, and enables the tent to obtain a long-lasting antibacterial effect.

[0020] Optionally, the organosilicon-modified waterborne polyurethane is prepared as follows: dehydrated PPG, PTMEG, PDMS, DHPDMS and DMBA are mixed, the temperature is increased, IPDI, BDO and DBTDL are added, the reaction is continued, TEA and water are added, the mixture is stirred and dispersed, and the mixture is distilled under reduced pressure to obtain a modified waterborne polyurethane.

[0021] By adopting the above technical scheme, preferably using PDMS and DHPDMS to modify the waterborne polyurethane, introducing silicone segments into the polyurethane, and grafting the silicone segments into the alkyl R in the waterborne polyurethane, the formation of easily hydrolyzed Si-OC segments in the waterborne polyurethane is avoided, so that the waterborne polyurethane obtains a higher water resistance effect.

[0022] Optionally, the mass ratio of PPG to PTMEG is 1-2:1.

[0023] By adopting the above technical scheme, the mass ratio of PPG to PTMEG is optimized. At an appropriate mass ratio, they can be sheared into smaller particles in the emulsification stage, and the regular segment structure of PTMEG is combined with the irregular segment structure of PPG to obtain a more regular segment structure in the antibacterial coating, thereby improving the density of the antibacterial coating and enabling the antibacterial coating to obtain a better hydrophobic effect.

[0024] Optionally, the antibacterial material includes graphene, titanium dioxide and nanosilver.

[0025] By adopting the above technical solution, graphene has a unique layered structure, so that graphene can form an overlapping and staggered layered structure in the antibacterial coating, that is, a shielding layer is formed on the surface of the antibacterial coating to isolate the external environment from the tent fabric. Titanium dioxide has an excellent photocatalytic effect, and the active free radicals generated by photocatalysis are used to destroy the nucleic acid of bacteria to obtain an excellent antibacterial effect. Titanium dioxide can be filled in the staggered sheet structure of graphene and fill the gaps between the graphene sheets, effectively improving the density of the antibacterial coating and further improving the hydrophobic effect of the antibacterial coating. Nanosilver can also fill the pore structure generated by graphene, and use free silver ions to pass through the bacterial cell membrane and bind to nucleic acids to eliminate bacteria. At the same time, nanosilver can produce a plasma resonance effect, generate photoelectrons and can be transferred to titanium dioxide, promoting photocatalysis of titanium dioxide, and further improving the antibacterial effect of the antibacterial coating.

[0026] Optionally, the titanium dioxide is loaded on the graphene, and the specific preparation is as follows: nano titanium dioxide and graphene oxide are mixed, ultrasonically treated, hydrothermally reacted, filtered, solid matter is retained, washed, and vacuum dried to obtain a product.

[0027] By adopting the above technical solution and using graphene to load nano-titanium dioxide, the filling effect of nano-titanium dioxide on the pores between graphene sheets can be further improved, and the graphene sheet structure can protect titanium dioxide and reduce the possibility of titanium dioxide agglomeration in antibacterial coatings. In addition, as an excellent electron acceptor, graphene can quickly transfer photogenerated electrons to its surface during the photocatalytic process, which can effectively inhibit the recombination of photogenerated electrons and photogenerated holes in titanium dioxide, further improving the antibacterial effect of antibacterial coatings.

[0028] Optionally, the filler includes bentonite and attapulgite.

[0029] By adopting the above technical solution, bentonite and attapulgite are preferably used as fillers. Both bentonite and attapulgite have a lamellar structure and can form a shielding layer with graphene to improve the water resistance of the antibacterial coating. In addition, nano-titanium dioxide can cooperate with bentonite and attapulgite to form a micro-nano structure on the surface of the antibacterial coating. A large amount of air is trapped between the micro-nano structures, reducing the liquid-solid contact area, thereby improving the hydrophobic effect of the antibacterial coating.

[0030] Optionally, the titanium dioxide is loaded on the attapulgite, and the specific preparation is as follows: nano titanium dioxide and attapulgite are mixed, ultrasonically treated, hydrothermally reacted, filtered, solids are retained, washed, and vacuum dried to obtain a product.

[0031] By adopting the above technical solution and using attapulgite to load titanium dioxide, the possibility of titanium dioxide agglomeration can be further reduced, and it is beneficial to form a uniformly dispersed micro-nano structure, so that the antibacterial coating obtains a uniform hydrophobic effect.

[0032] Optionally, the attapulgite is loaded with nanosilver, and the attapulgite is prepared as follows: take the attapulgite and place it in hydrochloric acid, stir and mix, cool and centrifuge, wash, dry, and sieve to obtain acidified attapulgite, stir the acidified attapulgite and silver nitrate, centrifuge, retain the solid, wash, and dry to obtain the product.

[0033] By adopting the above technical solution, the fibrous crystal structure in the attapulgite can form an interlaced network structure in the antibacterial coating, thereby improving the compactness of the antibacterial coating. By using the attapulgite to load nanosilver, the dispersion effect of nanosilver in the antibacterial coating is improved, so that the antibacterial coating obtains a uniform antibacterial effect.

[0034] Optionally, the bentonite is loaded with rare earth lanthanum.

[0035] By adopting the above technical solution, the porous structure of bentonite is used to load rare earth lanthanum, which can combine with the RNA of bacteria to destroy the cell structure and thus play an antibacterial effect. When the filler is dispersed in the antibacterial coating, it can load the antibacterial particles and disperse them evenly, so that the antibacterial coating can obtain a uniform antibacterial effect. The introduction of rare earth lanthanum can also enable the antibacterial coating to obtain excellent heat insulation and near-infrared reflection effects, so that the tent tarpaulin has multifunctional characteristics.

[0036] In summary, this application has the following beneficial effects:

[0037] 1. Since the present application uses silicone-modified waterborne polyurethane as the main component material of the antibacterial coating, the introduction of silicone segments can make the waterborne polyurethane obtain better water resistance, and thus make the antibacterial coating obtain excellent water resistance and water washability, so that the tent can maintain the integrity of the coating during long-term use, and the coating is not easy to be washed and peeled off, that is, the antibacterial coating has a long-term antibacterial effect. It is preferred to pre-treat the base fabric, and the surface of the base fabric pre-treated by plasma obtains more active groups, which effectively improves the bonding effect between the base fabric and the antibacterial coating, further reduces the possibility of the antibacterial coating falling off, and enables the tent to obtain a long-term antibacterial effect.

[0038] 2. Titanium dioxide has an excellent photocatalytic effect in this application. The active free radicals generated by photocatalysis are used to destroy the nucleic acid of bacteria, and an excellent antibacterial effect is obtained. Titanium dioxide can be filled in the interlaced layer structure of graphene, filling the gaps between the graphene layers, effectively improving the compactness of the antibacterial coating, and further improving the hydrophobic effect of the antibacterial coating. Nanosilver can also fill the pore structure generated by graphene, and use free silver ions to pass through the bacterial cell membrane to bind nucleic acids to eliminate bacteria. At the same time, nanosilver can produce a plasma resonance effect, generate photoelectrons and can be transferred to titanium dioxide, promote photocatalysis of titanium dioxide, and further improve the antibacterial effect of the antibacterial coating.

[0039] 3. In this application, bentonite and attapulgite are used as fillers. Both bentonite and attapulgite have a lamellar structure and can form a shielding layer with graphene to improve the water resistance of the antibacterial coating. Nano-titanium dioxide can cooperate with bentonite and attapulgite to form a micro-nano structure on the surface of the antibacterial coating. A large amount of air is trapped between the micro-nano structures, reducing the liquid-solid contact area, thereby improving the hydrophobic effect of the antibacterial coating. DETAILED DESCRIPTION

[0040] The present application is further described in detail below with reference to the embodiments.

[0041] Preparation Example

[0042] Preparation example of silicone modified waterborne polyurethane

[0043] Preparation Example 1, PPG / PTMEG is added to a four-necked flask at a ratio of 1:2, and then 5.0% DHPDMS and 5.0% hydrophilic chain extender DMBA are added, the temperature is raised to 80°C, the initial R value is adjusted to 1.5, IPDI is slowly dripped, and after the dripping is completed, a small molecule chain extender BDO is added, and a catalyst DBTDL is added at the same time; after the reaction is continued at 80°C for 2 hours, the temperature is reduced to 40°C, TEA is added according to the neutralization degree of 100%, and neutralization is performed to form a salt for 15 minutes, and deionized water is added for high-speed emulsification and dispersion for 30 minutes; a measured amount of EDA is added under ice bath conditions and the chain extension reaction is carried out for 2 hours; finally, the residual acetone is removed by vacuum rotary evaporation to obtain a water-based polyurethane coating agent with a solid content of about 35%.

[0044] Preparation Example 2, PPG / PTMEG are added to a four-necked flask at a ratio of 1:1, and then 5.0% DHPDMS and 5.0% hydrophilic chain extender DMBA are added, the temperature is raised to 80°C, the initial R value is adjusted to 1.5, IPDI is slowly dripped, and after the dripping is completed, a small molecule chain extender BDO is added, and a catalyst DBTDL is added at the same time; after the reaction is continued at 80°C for 2 hours, the temperature is reduced to 40°C, TEA is added according to the neutralization degree of 100%, and neutralization is performed to form a salt for 15 minutes, and deionized water is added for high-speed emulsification and dispersion for 30 minutes; a measured amount of EDA is added under ice bath conditions and the chain extension reaction is carried out for 2 hours; finally, the residual acetone is removed by vacuum rotary evaporation to obtain a water-based polyurethane coating agent with a solid content of about 35%.

[0045] Preparation Example 3, take 5g of nano titanium dioxide and 5g of graphene oxide respectively, add 5L of ultrapure water and 2.5L of anhydrous ethanol, ultrasonically disperse for 1h, stir for 2h, and obtain a dark gray uniformly dispersed suspension, which is transferred into a hydrothermal reactor, reacted at 180°C for 12h, then filtered, the solid matter is retained, washed, and dried at 50°C for 6h to obtain the product.

[0046] Preparation Example 4, take 5g of nano titanium dioxide and 5g of attapulgite respectively, add 5L of ultrapure water and 2.5L of anhydrous ethanol, ultrasonically disperse for 1h, stir for 2h to obtain a uniformly dispersed suspension, transfer it into a hydrothermal reactor, react at 180°C for 12h, filter the reaction solution, retain the solid, wash, and dry at 50°C for 6h to obtain the product.

[0047] Preparation Example 5, take attapulgite and place it in 1 mol / L hydrochloric acid, the solid-liquid ratio is 1:10, the temperature is set to 80 ° C, the rotation speed is 500 r / min, and the magnetic stirrer is stirred for 1.5 hours. Cool and centrifuge, wash until the supernatant is neutral, dry at 110 ° C, and pass through a 180 mesh sieve to obtain acidified attapulgite. 5g of acidified attapulgite and 40mL of silver nitrate (0.2mol / L) are stirred, centrifuged, the solid is retained, washed, and dried to obtain the product.

[0048] Preparation Example 6: Take 1 g of rare earth lanthanum and 5 g of bentonite, stir and mix, add 5 L of ultrapure water, stir and disperse to obtain a dispersion, add 0.5 g of hexadecyltrimethylamine, continue stirring, filter, sieve, and dry to obtain bentonite loaded with rare earth lanthanum.

[0049] Example

[0050] Embodiments 1-3, the present application provides a method for preparing an antibacterial tent fabric, comprising a base fabric and an antibacterial coating coated on the surface of the base fabric, wherein the antibacterial coating comprises the following raw materials: waterborne polyurethane, antibacterial material, filler, polyacrylic acid dispersion, defoamer, lubricant, isocyanate curing agent; the waterborne polyurethane is the organosilicon-modified waterborne polyurethane prepared in Preparation Example 1; the antibacterial material comprises equal amounts of graphene, titanium dioxide and nanosilver, and the filler comprises equal amounts of bentonite and attapulgite. The lubricant is polyethylene wax, and the defoamer is polydimethylsiloxane.

[0051] The preparation of the antibacterial tent fabric comprises the following steps:

[0052] S1. Preparation of antibacterial coating: taking waterborne polyurethane, antibacterial material, filler, polyacrylic acid dispersion, defoamer, lubricant and isocyanate curing agent respectively by weight, stirring and mixing to obtain antibacterial coating;

[0053] S2, base fabric pretreatment: performing plasma treatment on the base fabric to obtain a pretreated base fabric;

[0054] S3. Tarpaulin preparation: coating the surface of the pretreated base fabric with an antibacterial coating, and drying the pretreated base fabric to prepare an antibacterial tent fabric.

[0055] Table 1 Composition of antibacterial coatings in Examples 1-3

[0056]

[0057]

[0058] Example 4 is different from Example 2 in that an equal mass of the organosilicon-modified waterborne polyurethane prepared in Preparation Example 2 is used to replace the waterborne polyurethane in Example 2 to prepare the antibacterial coating.

[0059] Example 5 is different from Example 2 in that the antibacterial material includes the product prepared in Preparation Example 3 and nanosilver in a mass ratio of 2:1 to prepare the antibacterial coating.

[0060] Example 6 is different from Example 2 in that the antibacterial material includes the product prepared in Preparation Example 3, nano titanium dioxide and nano silver in a mass ratio of 3:1:2, and the filler includes the product prepared in Preparation Example 4 and bentonite in equal amounts.

[0061] Example 7 differs from Example 2 in that the antibacterial material includes the product prepared in Preparation Example 3, nano titanium dioxide and nano silver in a mass ratio of 3:1:2, and the filler includes the product prepared in Preparation Example 4, the product prepared in Preparation Example 5 and bentonite in a mass ratio of 1:1:2.

[0062] Example 8 differs from Example 2 in that the antibacterial material includes the product prepared in Preparation Example 3, nano titanium dioxide and nano silver in a mass ratio of 3:1:2, and the filler includes the product prepared in Preparation Example 4, the product prepared in Preparation Example 5 and the product prepared in Preparation Example 6 in a mass ratio of 1:1:2.

[0063] Comparative Example

[0064] Comparative Example 1: This comparative example is different from Example 2 in that an equal mass of waterborne polyurethane is used in this comparative example to replace the silicone-modified waterborne polyurethane in Example 2.

[0065] Performance testing

[0066] (1) Hydrostatic pressure resistance test: Use a digital water permeability tester to test in accordance with the standard "Hydrostatic pressure method for testing and evaluating the waterproof performance of textiles" (GB / T4744-2013). Place the coating surface of the fabric downward and, under standard atmospheric conditions, subject the coating surface to a continuously rising water pressure until three water seepage points appear on the other side. Record the pressure value when the third water seepage point appears, and use this value to evaluate the hydrostatic pressure resistance of the sample.

[0067] (2) Antibacterial performance test: Test the antibacterial effect and durability of the tarpaulin according to "HG / T3950-2007".

[0068] Table 2 Performance test

[0069]

[0070] Combining the performance test comparison in Table 2, we can find that:

[0071] 1. By comparing Examples 1-3 with Comparative Example 1, it can be found that the water resistance and antibacterial durability of the tarpaulins prepared in Examples 1-3 are improved, which shows that in this application, organic silicon-modified waterborne polyurethane is used as the main component material of the antibacterial coating, and the introduction of organic silicon segments enables the waterborne polyurethane to obtain better water resistance, thereby enabling the antibacterial coating to obtain excellent water resistance and water washing resistance. The base fabric is pretreated, and the surface of the base fabric pretreated by plasma obtains more active groups, which effectively improves the bonding effect between the base fabric and the antibacterial coating, so that the tent obtains a long-lasting antibacterial effect. Titanium dioxide has an excellent photocatalytic effect, and can be filled in the interlaced lamellar structure of graphene, improve the compactness of the antibacterial coating, and further improve the hydrophobic effect of the antibacterial coating. Nanosilver can also fill the pore structure generated by graphene. At the same time, nanosilver can produce a plasma resonance effect, generate photoelectrons and can be transferred to titanium dioxide, promote photocatalysis of titanium dioxide, and further improve the antibacterial effect of the antibacterial coating.

[0072] 2. By comparing Example 4 with Example 2, it can be found that the water resistance and antibacterial durability of the tarpaulin prepared in Example 4 are reduced. This shows that in the present application, the regular segment structure of PTMEG can be combined with the irregular segment structure of PPG, thereby optimizing the mass ratio of PPG to PTMEG, so that a more regular segment structure is obtained in the antibacterial coating, that is, the density of the antibacterial coating is improved, so that the antibacterial coating obtains a better hydrophobic effect.

[0073] 3. By comparing Examples 5-6 with Example 2, it can be found that the water resistance and antibacterial durability of the tarpaulins prepared in Examples 5-6 are improved, which shows that the use of graphene to load nano-titanium dioxide in this application can further improve the filling effect of nano-titanium dioxide on the pores between graphene sheets, and the graphene sheet structure can protect titanium dioxide and reduce the possibility of titanium dioxide agglomeration in the antibacterial coating. In addition, as an excellent electron acceptor, graphene can quickly transfer photogenerated electrons to its surface during the photocatalytic process, which can effectively inhibit the recombination of photogenerated electrons and photogenerated holes in titanium dioxide, further improving the antibacterial effect of the antibacterial coating.

[0074] 4. By comparing Examples 7-8 with Example 2, it can be found that the water resistance and antibacterial durability of the tarpaulin prepared in Example 4 are improved, which shows that the fibrous crystal structure in attapulgite used in this application can form an interlaced network structure in the antibacterial coating, thereby improving the compactness of the antibacterial coating. The nanosilver is loaded with attapulgite to improve the dispersion effect of the nanosilver in the antibacterial coating, so that the antibacterial coating obtains a uniform antibacterial effect. The porous structure of bentonite is used to load rare earth lanthanum, so that the filler can load the antibacterial particles uniformly when dispersed in the antibacterial coating, thereby obtaining a uniform antibacterial effect. The introduction of rare earth lanthanum can also enable the antibacterial coating to obtain excellent thermal insulation and near-infrared reflection effects, so that the tent tarpaulin obtains multifunctional characteristics.

[0075] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing an antibacterial tent fabric, characterized in that: It comprises a base fabric and an antibacterial coating coated on the surface of the base fabric, wherein the antibacterial coating comprises the following raw materials in parts by weight: 40-45 parts of waterborne polyurethane; 5-15 parts of antibacterial materials; 10-20 parts of filler; 5-10 parts of polyacrylic acid dispersion; 1-2 parts of defoaming agent; 1-3 parts of lubricant; 1-3 parts of isocyanate curing agent; The waterborne polyurethane is silicone-modified waterborne polyurethane; The preparation of the antibacterial tent fabric comprises the following steps: S1. Preparation of antibacterial coating: taking waterborne polyurethane, antibacterial material, filler, polyacrylic acid dispersion, defoamer, lubricant and isocyanate curing agent respectively by weight, stirring and mixing to obtain antibacterial coating; S2, base fabric pretreatment: performing plasma treatment on the base fabric to obtain a pretreated base fabric; S3. Tarpaulin preparation: coating the surface of the pretreated base fabric with an antibacterial coating, and drying the pretreated base fabric to prepare an antibacterial tent fabric.

2. The method for preparing an antibacterial tent fabric according to claim 1, characterized in that: The organosilicon-modified waterborne polyurethane is prepared as follows: dehydrated PPG, PTMEG, PDMS, DHPDMS and DMBA are mixed, heated, IPDI, BDO and DBTDL are added, the reaction is continued, TEA and water are added, stirred and dispersed, and reduced pressure distillation is performed to obtain modified waterborne polyurethane.

3. The method for preparing an antibacterial tent fabric according to claim 2, characterized in that: The mass ratio of the PPG to PTMEG is 1-2:

1.

4. The method for preparing an antibacterial tent fabric according to claim 3, characterized in that: The antibacterial material includes graphene and titanium dioxide.

5. The method for preparing an antibacterial tent fabric according to claim 4, characterized in that: The titanium dioxide is loaded on the graphene, and is specifically prepared as follows: nano titanium dioxide and graphene oxide are mixed, ultrasonically treated, hydrothermally reacted, filtered, solids are retained, washed, and vacuum dried to obtain a product.

6. The method for preparing an antibacterial tent fabric according to claim 4, characterized in that: The filler includes bentonite and attapulgite.

7. The method for preparing an antibacterial tent fabric according to claim 6, characterized in that: The titanium dioxide is loaded on the attapulgite, and the specific preparation is as follows: nano titanium dioxide and attapulgite are mixed, ultrasonically treated, hydrothermally reacted, filtered, solids are retained, washed, and vacuum dried to obtain a product.

8. The method for preparing an antibacterial tent fabric according to claim 6, characterized in that: The attapulgite is loaded with nanosilver, and the preparation of the attapulgite is as follows: taking the attapulgite and placing it in hydrochloric acid, stirring and mixing, cooling and centrifuging, washing, drying, and sieving to obtain acidified attapulgite, stirring the acidified attapulgite and silver nitrate, centrifuging, retaining the solid, washing, and drying to obtain the product.

9. The method for preparing an antibacterial tent fabric according to claim 6, characterized in that: The bentonite is loaded with rare earth lanthanum.